Divergence between facial expressions and self-reported emotions: Sex differences in responses to video-based emotional stimuli - Sunyoung Choi; Changjin Jung; Jieun Kim; Sungsil Ko; Jiyoun Choi; Hyungjun Kim (PLoS ONE, 2026)
Emotional responses involve multiple components, including subjective experience and behavioral expression, which do not always align. Moreover, sex differences in emotional processing appear to vary across emotion types and response modalities. This study investigated sex differences and concordance between self-reported emotional experience and facial expressions elicited by naturalistic emotional video stimuli in a Korean adult sample. One hundred forty-eight healthy adults viewed video clips inducing joy, anxiety, sadness, and neutral states; spontaneous facial expressions were recorded and analyzed using the iMotions automated facial expression analysis software. After watching the stimuli, participants rated their subjective emotional experiences on discrete emotion scales (joy, sadness, disgust, fear/anxiety) and affective dimension scales (valence and arousal). Facial expression measures were summarized as positive and negative expressions. Age effects were statistically controlled for both facial expression and self-rating measures, and non-parametric analyses were conducted on the age-adjusted values because most variables deviated from normality. The video stimuli reliably elicited their intended target emotions in both self-reported ratings and facial expression patterns. Females exhibited stronger positive facial expressions than males during joyful stimuli despite comparable self-reported joy ratings. For anxiety stimuli, females showed higher fear/anxiety ratings and stronger negative facial expressions, whereas for sadness stimuli, females reported higher sadness ratings without corresponding differences in facial expressions. Females also reported higher arousal than males for negative stimuli. Concordance between facial expressions and self-reported ratings varied by emotion and sex, with robust associations for joy across both sexes, weaker or absent associations for sadness, and sex-specific associations for anxiety. These findings demonstrate that sex differences in emotional responding are emotion-specific and component-specific, highlighting partial dissociations between subjective experience and expressive behavior. This study provides culturally specific validation of dynamic video-based emotion paradigms and supports continuous facial expression analysis as an objective complement to self-report measures in Korean populations.